Further exploring the dynamicity, situatedness, and emergence of the self: The key role of context - Serafini, Ellen J. (Studies in Second Language Learning and Teaching, 2020)
Drawing on theoretical insights from a complex dynamic systems framework, this work explores the ways that learner selves, as they relate to learning and using languages, manifest across different contexts and timescales and emerge in interaction with various factors. First, a broad overview of dynamically-oriented L2 motivation research is provided before critically considering the need for research that aligns with conceptual advances made under the dynamic turn in SLA. In particular, this critical overview highlights a crucial need for more research employing dynamic methods capable of revealing how learner perceptions of self emerge in relation to their interlocutors and in interaction with external factors, including language ideologies that may uniquely characterize sociocultural contexts where target languages other than English are learned. The chapter concludes by discussing ways to implement dynamically oriented methodology that can provide much needed insights into the inherent dynamic, emergent, and contextually and socially embedded nature of learner selves.